2013
DOI: 10.1016/j.molcel.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Protons as Second Messenger Regulators of G Protein Signaling

Abstract: Summary In response to environmental stress cells often generate pH signals that serve to protect vital cellular components and reprogram gene expression for survival. A major barrier to our understanding of this process has been the identification of signaling proteins that detect changes in intracellular pH. To identify candidate pH sensors we developed a computer algorithm that searches proteins for networks of proton-binding sidechains. This analysis indicates that Gα subunits, the principal transducers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
121
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(136 citation statements)
references
References 44 publications
12
121
2
Order By: Relevance
“…3B) coincides with the loss of an internal proton-sensing network located at the interface of the Ras and helical domains of Gαs (Fig. 3B) (22). Likewise, the network buried within M2R is linked to a network of ionizable residues residing in its bound G protein-mimetic nanobody (Fig.…”
Section: Significancementioning
confidence: 60%
See 3 more Smart Citations
“…3B) coincides with the loss of an internal proton-sensing network located at the interface of the Ras and helical domains of Gαs (Fig. 3B) (22). Likewise, the network buried within M2R is linked to a network of ionizable residues residing in its bound G protein-mimetic nanobody (Fig.…”
Section: Significancementioning
confidence: 60%
“…functions, including oxygen delivery by hemoglobin (13), pH-gated ion transport (19,20), and signaling by pH-sensing (protonactivated) GPCRs (21) and G proteins (22).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, any pH change can cause a shift of the equilibrium, enriching protonated/relaxed species or deprotonated/retracted species. pHsensitive conformational switches have been reported for many other proteins (25)(26)(27). It has also been reported that K48-linked diubiquitin switches from a closed conformation to a predominant open conformation at pH 4.5 (28,29).…”
Section: Discussionmentioning
confidence: 83%